Physiological and morphological responses of Arabica coffee cultivars to soil compaction - Elísia Gomes Ramos; Vanessa Maria de Souza Barros; José Danizete Brás Miranda; Laís Maria Rodrigues Silva; Júlio Cesar Lima Neves; Renata Maria Strozi Alves Meira; Teogenes Senna de Oliveira (Revista Brasileira de Ciência do Solo, 2023)
ABSTRACT Compaction caused by mechanization affects soil quality and, consequently, the development of crops. This study aimed to evaluate the effect of different degrees of soil compaction on the physiology, morphology, and anatomy of different coffee cultivars in a controlled environment. The experiment was carried out in a greenhouse, with randomized block design in a 5 × 5 factorial arrangement, with five coffee cultivars (Arara, Catuaí Amarelo IAC 62, Catuaí Vermelho 144, MGS Paraíso 2 and Mundo Novo IAC 379-19) and five degrees of compaction (68, 74, 80, 86 and 92 %), with four repetitions, totaling 100 experimental units. The following variables were evaluated in the aboveground biomass: plant height, number of leaves, diameter of the orthotropic branch, fresh mass of leaves and stem, leaf area, gas exchange, and chlorophyll a and b index; in the roots: length, surface area, volume, diameter of fine and coarse roots, fresh and dry mass of roots, as well as anatomical characteristics. Results showed that soil with degrees of compaction above 80 % negatively affected the variables evaluated. Catuaí Vermelho 144 presented the worst performance regardless of the degree of compaction, while Arara and MGS Paraíso 2 showed the best performance under the evaluated compaction degrees. Anatomical structure of the roots was modified with soil compaction, and no differences were observed among cultivars.